Insect Species Diversity in Bangek River Area Lubuk Minturun Padang - Laselvy, Khairunnisa; Zulyusri, Zulyusri (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2024)
The study employed the insect net method to sample insects from the Bangek River. Primary and secondary data were collected for analysis. The research was conducted at Bangek River, Lubuk Minturun District, Padang City, West Sumatra Province. Insect sampling involved a single event using an insect net within the administrative area of Lubuk Minturun. A total of 35 insects were captured from the Bangek River, comprising 5 species from the Lepidoptera order, 28 from the Odonata order, and 1 species each from the Hemiptera and Orthoptera orders.